INTEGRATING TORAJA CULTURAL ELEMENTS IN SENTENCE WRITING: ENHANCING ENGLISH EDUCATION FOR STUDENTS AT UKI TORAJA - Tandi Arrang, Judith Ratu; Patanduk, Sushy Teko; Siumarlata, Viktor; Ba’dung, Yabes; Veronika, Veronika; Cherady, Jones (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
This study examines the integration of Toraja cultural elements in the sentence writing of English Education students at UKI Toraja. Using a quantitative descriptive analysis with 56 participants, the research utilized a questionnaire to evaluate engagement with local cultural aspects. The results show a significant incorporation of traditional food and natural landscapes, which received mean scores of 59 and 63, respectively, indicating students' appreciation for their heritage and enhancing their identity through sensory experiences. However, cultural expressions such as Londe/Pantun and the Rambu Tuka’ ceremony were less represented, with mean scores of 41 and 52, revealing gaps in students' familiarity and confidence. These findings highlight the need for educational initiatives that encourage the exploration of underrepresented cultural elements, thereby enriching student narratives and providing a more comprehensive portrayal of Toraja culture. Expanding curricular approaches to include diverse expressions of local heritage can improve writing skills and strengthen cultural connections among students.